ANALISIS TENAGA PUSTAKAWAN DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA MANADO - Bago, Syukurman Dearjoy; Masengi, Evi E.; Tumbel, Goinpeace (Gapenas Publisher, 2025)
This article examines the needs and roles of librarians at the Library and Archives Office of Manado City in supporting the quality of local library services. This study employs a qualitative approach using in-depth interviews, direct observation, and document analysis. The findings reveal a mismatch between the ideal and actual number of available librarians. Many librarians do not possess an educational background in library science and are required to perform multiple tasks, which negatively impacts service quality, limits service innovation, and reduces the effectiveness of literacy programs. Furthermore, the challenges include limited budgets, lack of training and regeneration, and recruitment policies that do not align with competency needs. This study suggests the need for strategic policies in librarian workforce planning, competency enhancement, and service evaluation systems aligned with national library standards.